Improved antimelanogenesis and antioxidant effects of polysaccharide from Cuscuta chinensis Lam seeds after enzymatic hydrolysis - Liu,Zi-Jun (2018)
Cuscuta chinensis polysaccharide (CPS) was extracted using hot water and enzymatically hydrolyzed C. chinensis polysaccharide (ECPS) was produced by the mannase enzymatic hydrolysis process. The purpose of this research was to investigate the antimelanogenic activity of ECPS and CPS in B16F10 melanoma cells. The in vitro antioxidant activity was assessed by their ferric iron reducing power and DPPH free radical scavenging activities. The molecular mass distribution of polysaccharides was determined using SEC-MALLS-RI. CPS was successfully enzymatically degraded using mannase and the weighted average molecular weights of CPS and ECPS were 434.6 kDa and 211.7 kDa. The results of biological activity assays suggested that the enzymatically hydrolyzed polysaccharide had superior antimelanogenic activity and antioxidant effect than the original polysaccharide. ECPS exhibited antimelanogenic activity by down-regulating the expression of tyrosinase, MITF, and TRP-1 without cytotoxic effects in B16F10 melanoma cells. In conclusion, ECPS have the potential to become a skin whitening product.